2016
DOI: 10.1016/j.jacc.2016.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Serial Changes in Cognitive Function Following Transcatheter Aortic Valve Replacement

Abstract: TAVR was associated with global improvement in cognitive status, more pronounced among those with cognitive impairment pre-TAVR. However, early decline in some complex cognitive functions was observed in one-quarter of TAVR recipients, persisting at 1 year in 10% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 34 publications
5
75
1
Order By: Relevance
“…Further, in light of emerging research, it is important to summarize the evolving patterns of AKI temporally, because with the currently available long‐term follow‐up data, unexpected possible benefits such as cognitive‐function improvement are being reported despite the presence of subclinical ischemia in patients who have undergone TAVR …”
Section: Importance and Definitionmentioning
confidence: 99%
“…Further, in light of emerging research, it is important to summarize the evolving patterns of AKI temporally, because with the currently available long‐term follow‐up data, unexpected possible benefits such as cognitive‐function improvement are being reported despite the presence of subclinical ischemia in patients who have undergone TAVR …”
Section: Importance and Definitionmentioning
confidence: 99%
“…2,3 Studies have generally shown no change in cognition or cognitive improvement at 3 to 6 months follow-up after TAVR. [4][5][6][7] According to other studies, inhospital postoperative delirium (IHPOD) is frequently observed early after TAVR 8,9 and is associated with prolonged hospital stay, readmission, and mortality after TAVR, thus being an important clinical concern. 8, 10,11 Delirium is an acute confusional state, characterized by disturbed consciousness, altered cognition, and inattention.…”
mentioning
confidence: 99%
“…This might be because of the older age of the participants in this study. In fact, the average MoCA‐J score in the present study did not differ from that of a study targeted at participants of the same age . The third limitation is that we could not take into account the duration of the loss of posterior occlusal support.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the average MoCA-J score in the present study did not differ from that of a study targeted at participants of the same age. 29 The third limitation is that we could not take into account the duration of the loss of posterior occlusal support. If the loss of posterior occlusal support is a burden on cognitive function, it is also important to know how long participants have been without posterior occlusal support.…”
Section: Discussionmentioning
confidence: 99%